Distributional Effects of Monetary Policy Shocks on Wage and Hours: Evidence from the Czech Labor Market - Monika Junicke; Jakub Matějů; Haroon Mumtaz; Angeliki Theophilopoulou (Prague University of Economics and Business, Faculty of International Relations (FIR), 2023)
We investigate the heterogeneity in the effects of monetary policy shocks on the distribution of wages and hours worked, using unique contract-level data from the Czech labor market and identifying monetary policy shocks using a narrative approach based on market suprises in interest rate futures. The results suggest that low-wage groups are hit more profoundly by monetary policy shocks than high-wage groups, and the effect of restrictive shocks is stronger in the manufacturing sector than in any other. Exploring other dimensions of the data oers insights into the heterogeneity of the impact of monetary policy on different demographic groups. We show that low-educated and also young workers are more affected by restrictive monetary policy shocks due to their higher shares in low-wage groups.
Keywords: E2; E3; E4; E5; 330; monetary policy; heterogeneity; wage inequality; shock identification